The Prime Minister’s power to give an order on the disciplinary proceedings against an alleged culprit whom the National Anti-Corruption Commission (the NACC) has passed a resolution finding a prima facie case for a disciplinary offence. - ระดาเขตร์ สรศักดิ์ (Thai Interdisciplinary and Sustainability Review, 2021)
Abstract Section 95 of the Organic Act on Counter Corruption B.E. 2542 (1999) specifies the important principles of the control measure for the disciplinary proceedings conducted by a superior or a person having the power to appoint or remove an alleged culprit. This is to ensure that such proceedings shall be taken in accordance with a disciplinary offence, which the NACC has passed a resolution that a prima facie case is found. In this regard, in the case where a superior or a person having the power to appoint or remove an alleged culprit fails to take the disciplinary action against such person for the offence in respect of, which the NACC has passed the resolution, without reasonable justification, or the NACC has opined that the disciplinary action is taken incorrectly or inappropriately, the NACC shall present its opinion to the Prime Minister and the Prime Minister shall have the power to issue an order on this matter as appropriate. The Prime Minister’s power under Section 95 shall therefore be exercised with thorough consideration of all aspects of the legal framework, giving the Prime Minister’s power to issue such order. Moreover, in the case where a superior of or a person having the power to appoint or remove an alleged culprit fails to take the disciplinary action for the offence in respect of, which the NACC has passed the resolution, or the disciplinary action is taken incorrectly or inappropriately, it must be considered as to whether there is any reasonable grounds for a superior of or a person having the power to appoint or remove an alleged culprit to do so. Nevertheless, although the Organic Act on Counter Corruption B.E. 2561 (2018) has already come into effect, the principles of the Prime Minister’s power to give an order on this matter remain the same as specified in the Organic Act on Counter Corruption B.E. 2542 (1999).